Sociological theory and concepts in public administration - Barnabas, A.P. (2008)
While sociology looks at society from the view points of social relations, public administration looks at in terms of administrative process and governance. The approach in this article is to look at some sociologists whose theories have relevance to certain concepts in the discipline of public administration. It is an effort to look at the interface between sociology and public administration. - Reproduced.
Keywords: Public administration